STRATEGI RUMAH SAKIT DALAM MENGELOLA PERSEDIAAN FARMASI SELAMA PANDEMI COVID-19 - Inaz Kemala Dewi; Helen Andriani (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Background: COVID-19 infection, which was declared a pandemic by WHO have a major impact on pharmaceutical sector. Drug shortage is one of the impacts that can affect the patient’s health and also hospital’s finances through prolonged patient care costs. The aim of this study is to assess hospital strategies to maintain pharmaceutical supply during the COVID-19 pandemic. Methods: This research is a literature review using the PRISMA method. A literature search was performed in Scopus, Science Direct, and Springer Link using keyword pharmaceutical supply COVID-19. Studies that published between 2020 – 2021, is in English, and discussed drug supply in hospital during the COVID-19 pandemic were included. Studies were excluded if it didn’t discuss drug supply in hospital during the COVID-19 pandemic and not available in full text. Results: A total of 3,242 articles were identified, of which 13 articles fully met the eligibility criteria and were the analyzed. Most of the studies (n=10) discussed the implementation of drug logistics during the pandemic, such as efficient drug planning, centralized drug storage, drug distribution with a unit-dose dispensing system, monitoring and reporting of drugs used every day through an appropriate database. The other three articles discuss the formation of a collaborative coordination team between medical personnel and the division of working hours on site and off site to help maintain drug supplies. Conclusions: Efficient drug planning and an integrated information system in reporting drug availability can maintain drug supply during the COVID-19 pandemic. Collaborative HR management has an important role in supporting drug supply control through division of labor with limited staff and working time.